2011
DOI: 10.1158/0008-5472.can-10-3277
|View full text |Cite
|
Sign up to set email alerts
|

Significance and Mechanism of Lymph Node Metastasis in Cancer Progression

Abstract: The effect of local therapy, such as surgical lymph node (LN) dissection and radiotherapy, on the survival of cancer patients has been debated for decades. Several lines of recent clinical evidence support that LN metastasis plays significant roles in systemic dissemination of cancer cells, although the effects of surgical LN dissection on survival was downplayed historically because of controversial data. Molecular studies of LN metastasis suggest that the microenvironment within LNs, including chemokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 38 publications
4
120
0
4
Order By: Relevance
“…[6][7][8][9][13][14][15] In CRC, it was reported that CXCR3 expression is upregulated in metastatic colon cancer cells, but not in their primary lesions, and that the CXCL10/CXCR3 axis…”
mentioning
confidence: 99%
“…[6][7][8][9][13][14][15] In CRC, it was reported that CXCR3 expression is upregulated in metastatic colon cancer cells, but not in their primary lesions, and that the CXCL10/CXCR3 axis…”
mentioning
confidence: 99%
“…2,37,44 However, tumors may manipulate the LN microenvironment to provide hospitable soil for the seeding and proliferation of tumor cells. 12 In the current study, we observed that levels of CD169 C CD8 C T cells were significantly lower in peri-LN than distant-LN, and the ratios of CD169 C CD8 C T cells in both peri-LN and distant-LN were higher in early stage CRC patients than those in advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tumors have been suggested to significantly modulate the microenvironment of LNs. 37,38,40 Thus, a better understanding of the mechanism of tumor-modulating CD169 C CD8 C T cells may be used to develop new cancer immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokinetic functions in the immune system, chemokines and their receptors also exert critical roles in tumor initiation, progression and metastasis (6). CRC cells have been shown to express the chemokine receptors, CXCR4 and CXCR3 (7)(8)(9)(10)(11)(12). In a clinical study, CXCR4 expression in CRC was revealed to increase the recurrence of the cancer, poor survival and liver metastasis (8).…”
Section: Introductionmentioning
confidence: 99%